El principio de preclusión de la pena y el derecho a la defensa en el juzgamiento de las contravenciones de tránsito. - Montenegro Mazón, Kennedy Euclides (2024)
The theme "THE PRINCIPLE OF PRECLUSION OF THE PENALTY AND THE RIGHT TO DEFENSE IN THE TRIAL OF TRAFFIC INFRINGEMENTS", corresponds to a preliminary study of a legal examination of the theory related to the evidentiary clauses, this is defined in the norms that govern traffic violations, for example, comprehensive organizational criminal law. The objective is to provide a more extensive approach to all people and lawyers interested in this topic, this particular rule of criminal procedure and traffic violations. It refers to the legal study of traffic violations and the probative elements in the development of their challenges are identified, as well as a comprehensive organization of regulations to address this issue of criminal justice reform. The compiled topics are intended to address real-world problems in the administration of justice that are of a transcendent nature and are found in its branch of criminal law, the Constitution of the Republic of Ecuador and the criminal law of the integral organization. Themes are designed to solve real problems. Instituted in a trial of a priori importance nature and address issues such as traffic violations in its criminal law branches, Constitution of the Republic and Organic Law, a prolific criminal. In this project the quantitative method will be used, the same that will allow technical and legal research on the estoppel of sentence and the right to defense and will address the aspects that will be used in the development of this research. Undoubtedly, each aspect is fundamental due to its helps in determining the type of research that is in the process of development starting from the selected topic and continuing with the research design, scope, population and sample of the work, the procedure for collecting data and the most appropriate method for the execution of this work. The results recommend reforms in article 644 of the Comprehensive Organic Criminal Code, so that in this way the term for challenging the summons ballot is extended and the probationary period is extended, which comply with the requirements of due process. Keywords: contravention, foreclosure, infractions, challenge.